Influence of Bank Syariah Indonesia's Instagram Social Media on Students' Interest in Saving at Bank Syariah Indonesia - Nurfajar, Budi; Sumarni, Sumarni; Ilmy, Rizky Maidan; Habibah, Tsuroyya Azhari (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, INDONESIA, 2023)
This study aims to determine the level of Instagram social media usage among students at Institut Agama Islam Darussalam Ciamis, and their interest in saving at Bank Syariah Indonesia (BSI). This study also measures the influence of BSI's Instagram social media on students' interest in saving at the bank. Using quantitative methods, data are analyzed numerically to test the relationship between variables. Descriptive methods provide a detailed description of the observed phenomena, including numerical data and characteristics. The results of the statistical analysis using SPSS show an R² value of 0.376, which means that 37.6% of students' savings interest is influenced by BSI's Instagram social media, while 62.4% is influenced by other variables not studied. The t-test shows a significant coefficient with a p-value less than 0.05, which indicates that there is a significant influence between BSI's Instagram social media on students' interest in saving at BSI. Therefore, the hypothesis that BSI's Instagram social media affects students' interest in saving is accepted.